Transformative Dialogue, Conflict, and Peacebuilding - El Halabi, Elias (The ecumenical review, 2024)
In the aftermath of the 11 September 2001, attacks, focus has shifted to dealing with religious fundamentalism and violence in the name of religion. Since religion was part of the problem, it needs to be part of the solution. The question is how interfaith dialogue can mitigate conflicts or resolve them as a crucial step toward building peace. Defining terminologies is a crucial step since the ambiguity generated about what is dialogue and the different perceptions of peace add to the complexity of the problem. This article introduces the different notions of peace and outlines the approaches to dealing with conflict. It argues that rethinking conflict is a key step and that transformation is the new paradigm. Transformative dialogue is essential to transforming conflict, thus leading to positive and sustainable peace. Interconnectedness, shared humanity and accountability are the foundations for the renewed interfaith partnership for sustainable peace.